1983
DOI: 10.1080/15287398309530400
|View full text |Cite
|
Sign up to set email alerts
|

Detection of nitroaromatic compounds on coal combustion particles

Abstract: Mutagenic and nonmutagenic extracts of fly ash from fluidized bed combustion were analyzed to determine the compounds responsible for the direct mutagenic activity (mutagenic activity that does not require added metabolic enzymes in the Salmonella mutagenicity assay). Some nitro derivatives of polycyclic aromatic hydrocarbons which are direct acting mutagens were detected by tandem triple quadrupole mass spectrometry. Treatment of a mutagenic and a nonmutagenic extract with excess N2O4 resulted in 28- and 3200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1984
1984
2020
2020

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Previous studies indicated that NACs mainly originate from BB, traffic or secondary formation in the gas or condensed phases, with minor contributions from coal combustion (Hanson et al, 1983;Wang et al, 2018;Yuan et al, 2016;Xie et al, 2019;Chow et al, 2016). While previous studies found that traffic has important effects on NAC levels (Cecinato et al, 2005;Tremp et al, 1993), its 5 influence appeared to be limited in this case: there was a weak to negative association between typical automobile exhaust VOCs (benzene, toluene, and trimethylbenzene) (Zhang et al, 2018;Geng et al, 2008;Batterman et al, 2002) and the studied NACs.…”
Section: Sources Of Nitro-aromatic Compoundsmentioning
confidence: 66%
“…Previous studies indicated that NACs mainly originate from BB, traffic or secondary formation in the gas or condensed phases, with minor contributions from coal combustion (Hanson et al, 1983;Wang et al, 2018;Yuan et al, 2016;Xie et al, 2019;Chow et al, 2016). While previous studies found that traffic has important effects on NAC levels (Cecinato et al, 2005;Tremp et al, 1993), its 5 influence appeared to be limited in this case: there was a weak to negative association between typical automobile exhaust VOCs (benzene, toluene, and trimethylbenzene) (Zhang et al, 2018;Geng et al, 2008;Batterman et al, 2002) and the studied NACs.…”
Section: Sources Of Nitro-aromatic Compoundsmentioning
confidence: 66%
“…In general organic compounds have been quantified in much higher concentrations in the vapor phase than in organic extracts of FBC particulate materials (Hanson et al 1980). GC/MS was used to tentatively identify organic compounds in dlchloromethane extracts of atmospheric FBC (AFBC) fly ash (Hanson et al 1983;Merryman et al 1977). Several classes of mutagenic organic compounds were identified in organic extracts from small experimental FBC, including 4-to 6-ring aromatic and highly polar compounds such as phenols, nitriles, ketones, and carboxylic acids (Kubitschek and Haugen 1980).…”
Section: Inorganic Chemical Composition Of Pcc Fly Ashmentioning
confidence: 99%
“…Nitro aromatic compounds, corresponding to products from the reactions between NOx and PAH previously determined in the sample by GC/MS, were tentatively identified using tandem mass spectrometry (MS/MS) to analyze extracts of FBC baghouse fly ash. Among these compounds were the dinitro-products of pyrene and fluoranthene, which were highly mutagenic in microbial frame-shift tests (Hanson et al 1983).…”
Section: Inorganic Chemical Composition Of Pcc Fly Ashmentioning
confidence: 99%
“…Other coal-derived "organics" not 10,26,40 mentioned in the Report are soot and unburned carbon associated with fly ash.…”
Section: Methods Of Analysismentioning
confidence: 99%